The Andean Swallow (Orochelidon andecola) in Argentina - Mazar Barnett, Juan (2014)
During ornithological studies in the provinces of Jujuy, Salta, and San Juan, we recorded the Andean Swallow Orochelidon andecola at 40 localities. These are the first records in Argentina, and also represent the southernmost for the species. Some of these localities are up to 1500 m lower than the previously known elevational limit (now 800 masl), and up to 1100 km southwards. This is a relatively poorly known swallow, and we present novel natural history data. We found evidence of breeding in five localities. We obtained photographs and tape recordings, and provide details of a specimen.